2003
DOI: 10.1081/jdi-120026042
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor 05 Provide Additional Values to C-Reactive Protein and Anti-myeloperoxidase Titer as a Parameter for Evaluating Disease Activity in Anti-myeloperoxidase Associated Vasculitis

Abstract: Anti-myeloperoxidase (anti-MPO) associated vasculitis can result in rapid clinical deterioration. Immunosuppressive therapy is effective but involving considerable toxicity, and disease relapse frequently ensues. Laboratory parameters, such as C-reactive protein and anti-MPO titer, have substantial values in monitoring disease activity. However, the sensitivity and specificity are not satisfactory. This report presents the case of an old man with anti-MPO associated vasculitis. A parallel correlation between s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…There has been several reports showing the clinical value of VEGF in monitoring disease activity in vasculitis including MPA. [24][25][26] Our result is compatible with previous reports and we propose that serum VEGF might become one of the serum markers that reflect disease activity of MPA. We also showed that serum VEGF levels in MPA patients were significantly higher than those in respiratory tract infection and urinary tract infection.…”
Section: Discussionsupporting
confidence: 92%
“…There has been several reports showing the clinical value of VEGF in monitoring disease activity in vasculitis including MPA. [24][25][26] Our result is compatible with previous reports and we propose that serum VEGF might become one of the serum markers that reflect disease activity of MPA. We also showed that serum VEGF levels in MPA patients were significantly higher than those in respiratory tract infection and urinary tract infection.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to the role of EGFR signaling in the AAV pathogenesis, our bioinformatic analysis also highlighted the inclusion of vascular endothelial growth factor (VEGF) signalization among the biological pathways regulated by the targets of miRNAs with elevated levels in uEVs in patients (Figure 3). This association was mentioned only in one case report, where the correlation between serum VEGF levels with C-reactive protein and anti-MPO titer was clearly demonstrated [44].…”
Section: Discussionmentioning
confidence: 99%
“…32 Studies have shown the clinical value of VEGF-A in monitoring disease activity in vasculitis, including MPA. 19,33 Shulman et al. 34 reported that VEGF-A expression is altered in many glomerular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…18 Correlations of VEGF-A concentrations with serum CRP (sCRP) and anti-myeloperoxidase (MPO) titres have been demonstrated; these suggest that VEGF-A is a potential marker for monitoring disease activity in anti-MPO-associated vasculitis. 19 However, the relationship between VEGF-A and VEGF-A 165 b concentrations and patient prognosis in longitudinal samples is unknown.…”
Section: Introductionmentioning
confidence: 99%